Challenges to promoting social inclusion of the extreme poor: Evidence from a large scale experiment in Colombia - Laura Abramovsky; Orazio Attanasio; Kai Barron; Pedro Carneiro; George Stoye (Institute for Fiscal Studies (IFS), 2014)
We evaluate the large scale pilot of an innovative and major welfare intervention in Colombia, which combines homes visits by trained social workers to households in extreme poverty with preferential access to social programs. We use a randomized control trial and a very rich dataset collected as part of the evaluation to identify program impacts on the knowledge and take-up of social programs and the labor supply of targeted households. We find no consistent impact of the program on these outcomes, possibly because the way the pilot was implemented resulted in very light treatment in terms of home visits. Importantly, administrative data indicates that the program has been rolled out nationally in a very similar fashion, suggesting that this major national program is likely to fail in making a significant contribution to reducing extreme poverty. We suggest that the program should undergo substantial reforms, which in turn should be evaluated.
Keywords: J08; I38; C93; 330; Social Exclusion; Social Protection; Colombia; Extreme Poverty; Labor Supply; Randomized Control Trial